Role of dehydration on sport performance and recommendations for rehydration - Vukašinović, Danka; Maksimović, Miloš; Tanasković, Slobodan (Medicinski podmladak, 2023)
The acute and chronic effects of dehydration on athletes' health are well known, but it is less known about the relationship between dehydration and sport performance. There is an overall consensus in literature that dehydration ≥2% body mass represents a threshold at which endurance, as aerobic performance, becomes impaired. Dehydration degrades aerobic performance by various mechanisms, such as decrease in VO2max, decrease in circulatory volume and consequent decrease in cardiac stroke volume. At higher levels of dehydration there is an increase in heart rate, body temperature, carbohydrate oxidation and muscle glycogenolysis.  The effect of dehydration on anaerobic sport performance, such as muscle straight and power, is less known. The high osmotic stress that usually accompanies high levels of intracellular dehydration can modulate the permeability of the blood-brain barrier, alter the neuronal firing of osmoreceptor cells in the hypothalamus, and potentially affect the excitability of motor output pathways. Studies have shown that acute dehydration impairs muscle strength and endurance and increases the perception of fatigue, but without changes in markers of central and peripheral neuromuscular function. In addition to the physical, dehydration also affects the mental performance of athletes. Symptoms of dehydration (dry mouth, thirst, headache, fatigue) affect the athletes' cognitive functions and their cognitive resilience. Therefore, personalized rehydration strategies play a key role in athletes' safety during sporting activities, as well as in optimizing sport performance. In this paper we review the role of dehydration on physical and mental athletes’ performance, as well as the lates recommendations for adequate rehydration.
Keywords: dehydration, sport performance, rehydration, recommendations